Polyethylene modified polyformaldehyde composite material and preparation method thereof

By introducing polyethylene, calcium carbonate and antioxidants into polyformaldehyde and melt blending, the problems of insufficient polyformaldehyde toughness and notch impact strength are solved, and the mechanical properties of the material are significantly improved.

CN119570192APending Publication Date: 2025-03-07TIANJIN BOHUA YONGLI CHEM IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411759980.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The notched impact strength of polyformaldehyde is not high and has low toughness, which limits its application areas. The existing modified material formulas still need to be optimized to improve the mechanical strength and performance of the material.

Method used

A method for preparing polyethylene modified polyformaldehyde composite material is adopted. Modified polyformaldehyde particles are obtained by mixing polyformaldehyde resin, polyethylene, calcium carbonate and antioxidant in a specific proportion and melt blending in a twin screw extruder.

Benefits of technology

The mechanical indicators of polyformaldehyde have been significantly improved, and the modified polyformaldehyde notched impact strength has been increased by 30.5%-70.8%, and its toughness has been significantly enhanced. It is suitable for processing products with high toughness and high notched impact strength.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a polyethylene modified polyformaldehyde composite material and a preparation method thereof, 88.7-94.2 parts of polyformaldehyde resin, 5-10 parts of polyethylene, 0.3-1 part of calcium carbonate and 0.2-0.4 part of antioxidant are put into a mixer to be mixed, the mixture is poured into a feeding machine after being uniformly mixed, the mixed material is sent into a double-screw extruder through the feeding machine, and the double-screw extruder is extruded to obtain the polyethylene modified polyformaldehyde composite material. The mixed material is subjected to melt blending and extrusion in a double-screw extruder, extruded polymer melt material strips are cooled and then enter a granulator to be cut into uniform particles, and the modified polyformaldehyde particles are obtained after drying. The notch impact strength of the modified polyformaldehyde is obviously improved from 4.7-6.3 kJ / m < 2 > to 7.62-8.56 kJ / m < 2 >, and is improved by 30.5%-70.8%. The formula composition of the composite material is precisely designed, so that the composite material has excellent strength and toughness, the production efficiency is continuously improved, and the performance and quality of a product are optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer processing, and relates to a polyethylene modified polyoxymethylene composite material and a preparation method thereof. Background Art

[0002] Polyoxymethylene (POM) is an excellent engineering plastic with high strength, high modulus, good dimensional stability, good creep resistance, fatigue resistance, wear resistance, chemical resistance and self-lubrication. However, its notched impact strength is not high and its toughness is low, which limits its application. In order to overcome its performance defects, POM is generally blended and modified to enhance its notched impact strength and make up for its low toughness, making it functional and practical.

[0003] Patent ZL200510020429.8 prepares ultrafine composite powder by compounding thermoplastic polyurethane elastomer with calcium carbonate, and then compounding it with POM. The obtained P0M has high impact toughness. However, due to the poor thermal stability of thermoplastic polyurethane elastomer, its molecules are easily degraded at high temperatures, resulting in a weakened toughening effect. In addition, although a higher amount of polyurethane elastomer can significantly increase the impact toughness of POM, it will lead to a significant reduction in its mechanical strength.

[0004] At present, the formula of polyoxymethylene modified materials still needs to be optimized to improve the mechanical strength of the material and optimize the performance and quality of the product. Summary of the invention

[0005] In view of the above problems, the present invention discloses a polyethylene-modified polyoxymethylene composite material and a preparation method thereof. The specific technical scheme is as follows:

[0006] A polyethylene modified polyoxymethylene composite material comprises, by weight, 88.7-94.2 parts of polyoxymethylene resin, 5-10 parts of polyethylene, 0.3-1 parts of calcium carbonate, and 0.2-0.4 parts of antioxidant; the total amount of the above components is 100 parts.

[0007] The antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 616.

[0008] The polyoxymethylene resin has a melt index of 7-11 g / 10 min, a tensile modulus of 2200-2600 MPa, and a notched impact strength of 4.7-6.3 kJ / m 2 .

[0009] The polyethylene melt index is 1.5-2.5 g / 10 min, and the density is 0.917-0.923 g / cm 3 , the tensile breaking stress is 11-15MPa.

[0010] The preparation method of the polyethylene modified polyoxymethylene composite material of the present invention comprises the following steps: putting 88.7-94.2 parts of polyoxymethylene resin, 5-10 parts of polyethylene, 0.3-1 parts of calcium carbonate and 0.2-0.4 parts of antioxidant into a mixer for mixing, pouring the mixture into a feeder after uniform mixing, sending the mixture into a twin-screw extruder through the feeder, and melting and blending the mixture in the twin-screw extruder and extruding the mixture. After cooling, the extruded polymer melt material strips enter a pelletizer for cutting into uniform particles, and after drying, the modified polyoxymethylene particles are obtained.

[0011] The feeder has a rotation speed of 140-180 rpm.

[0012] The rotation speed of the twin-screw extruder is 220-260 rpm, and the temperature of the twin-screw extruder is controlled at 170-200°C.

[0013] The specific instructions are as follows:

[0014] The antioxidant of the polyethylene-modified polyoxymethylene composite material is one or more of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 616, and the addition thereof can improve the weather resistance thereof.

[0015] Preferably, the raw materials for its preparation include, by weight: 89.8 parts of polyoxymethylene resin, 9 parts of polyethylene, 0.9 parts of calcium carbonate, and 0.3 parts of antioxidant.

[0016] The polyoxymethylene resin model is MC90, which comes from Tianjin Bohai Yongli Chemical Co., Ltd. and has a melt index of 7-11 g / 10 min.

[0017] Preferably, the added amount of polyethylene is 9 parts, the added amount of calcium carbonate is 0.9 parts, the antioxidant is 1010, and the added amount of antioxidant 1010 is 0.3 parts.

[0018] Preferably, the speed of the twin-screw extruder is 240 rpm, the speed of the feeder is 160 rpm, and the temperature of the twin-screw extruder is controlled at 185°C.

[0019] Another aspect of the invention discloses a method for preparing the modified polyoxymethylene composite material, which comprises the steps of batching, mixing, extruding, cooling, pelletizing and drying.

[0020] The batching process is as follows: according to the product formula requirements, the prepared raw materials are batched in a certain proportion to obtain a mixed material.

[0021] Furthermore, the mixing process is: putting polyoxymethylene resin, polyethylene, calcium carbonate and antioxidant into a mixer, and after mixing evenly, obtaining a mixed material.

[0022] The extrusion process is as follows: feeding by a feeder, heating by a twin-screw extruder to melt and blend the mixed materials, making various components uniformly dispersed in the polymer, and extruding the polymer melt.

[0023] Furthermore, the cooling process is as follows: the extruded polymer melt strands are immersed in cooling water for cooling.

[0024] Furthermore, the pelletizing process is: cutting the cooled material strips into plastic pellets of uniform size.

[0025] Beneficial Effects

[0026] 1. The present invention improves the mechanical indexes of existing polyoxymethylene, and the notched impact strength of the modified polyoxymethylene is 7.62-8.56 kJ / m 2 Compared with the unmodified notched impact strength, the notched impact strength is increased by 30.5%-70.8%, and the toughness is significantly enhanced. This material can be used to process products with high requirements for toughness and notched impact strength.

[0027] 2. The present invention accurately designs the formula composition of the composite material so that the composite material can have excellent strength and toughness while continuously improving production efficiency and optimizing product performance and quality. DETAILED DESCRIPTION

[0028] Example 1

[0029] This embodiment 1 discloses a polyethylene modified polyoxymethylene composite material, which is prepared from the following raw materials by weight: 89.8 parts of polyoxymethylene resin, 9 parts of polyethylene, 0.9 parts of calcium carbonate, and 0.3 parts of antioxidant 1010. The polyoxymethylene resin comes from Tianjin Bohai Yongli Chemical Co., Ltd., and its model is MC90. Its melt index is 9g / 10min, tensile modulus is 2400MPa, and notched impact strength is 5.5kJ / m 2 The polyethylene was purchased from Jilin Chemical Co., Ltd. Its melt index was 2.0 g / 10 min and its density was 0.92 g / cm 3 , the tensile breaking stress is 12MPa. Calcium carbonate was purchased from Changzhou Lehuan Co., Ltd.

[0030] This embodiment 1 discloses a method for preparing the modified polyformaldehyde composite material, the steps are: drying the polyformaldehyde resin before batching. Put the above-mentioned materials into a mixer and mix them. After mixing evenly, pour them into a feeder, and send the mixed material to a twin-screw extruder through the feeder. The feeder speed is 160rpm. The mixed material is melt-blended and extruded in the twin-screw extruder. The speed of the twin-screw extruder is 240rpm and the temperature is 185°C. After cooling, the extruded polymer melt material strips enter a pelletizer and are cut into uniform particles. After drying, the modified polyformaldehyde particles are obtained.

[0031] The evaluation method of the embodiment is as follows: the melt index is measured by Zwick Aflow melt index meter, the dried polyoxymethylene resin is preheated at 190°C for 5 minutes, and a load of 2.16 kg is applied for testing, and the test complies with ISO-1133 standard. The basic mechanical properties are measured by Zwick universal testing machine, and the tensile modulus and tensile strain are tested according to ISO-527; the notched impact strength is tested according to ISO-179-1 / 1e A. The notched impact strength of the modified polyoxymethylene particles is 8.56 kJ / m 2 The notched impact strength is increased by 55.6% compared with that before modification; the melt index is 8.09g / 10min, the tensile modulus is 2220MPa, and the tensile strain is 46%. The melt index and tensile modulus have not changed significantly.

[0032] Example 2

[0033] This embodiment 2 discloses a polyethylene modified polyoxymethylene composite material, which is prepared from 93.6 parts of polyoxymethylene resin, 5 parts of polyethylene, 1 part of calcium carbonate, and 0.4 parts of antioxidant 1076 by weight. The polyoxymethylene resin comes from Tianjin Bohai Yongli Chemical Co., Ltd., and its model is MC90. Its melt index is 9g / 10min, tensile modulus is 2400MPa, and notched impact strength is 5.5kJ / m 2 The polyethylene was purchased from Jilin Chemical Co., Ltd. Its melt index was 2.0 g / 10 min and its density was 0.92 g / cm 3 , the tensile fracture stress is 12MPa.

[0034] The above materials are put into a mixer and mixed. After being mixed evenly, they are poured into a feeder. The mixed materials are fed to a twin-screw extruder through the feeder. The speed of the feeder is 160 rpm. The mixed materials are melted, blended and extruded in the twin-screw extruder. The speed of the twin-screw extruder is 240 rpm and the temperature is 185°C. After the extruded polymer melt is cooled, it enters a pelletizer and is cut into uniform particles. After drying, the modified polyoxymethylene particles are obtained.

[0035] The evaluation method of the embodiment is as follows: the melt index is measured by Zwick Aflow melt index meter, the dried polyoxymethylene resin is preheated at 190°C for 5 minutes, and a load of 2.16 kg is applied for testing, and the test complies with ISO-1133 standard. The basic mechanical properties are measured by Zwick universal testing machine, and the tensile modulus and tensile strain are tested according to ISO-527; the notched impact strength is tested according to ISO-179-1 / 1e A. The notched impact strength of the modified polyoxymethylene particles is 8.17 kJ / m 2The notched impact strength is increased by 48.5% compared with that before modification; the melt index is 7.93g / 10min, the tensile modulus is 2230MPa, and the tensile strain is 42%. The melt index and tensile modulus have not changed significantly.

[0036] Example 3

[0037] This embodiment 3 discloses a polyethylene modified polyoxymethylene composite material, which is prepared from 90.5 parts of polyoxymethylene resin, 9 parts of polyethylene, 0.3 parts of calcium carbonate, and 0.2 parts of antioxidant 616 by weight. The polyoxymethylene resin comes from Tianjin Bohai Yongli Chemical Co., Ltd., and its model is MC90. Its melt index is 7g / 10min, tensile modulus is 2200MPa, and notched impact strength is 4.7kJ / m 2 The polyethylene was purchased from Jilin Chemical Co., Ltd. Its melt index was 1.5 g / 10 min and its density was 0.917 g / cm 3 , the tensile breaking stress is 11MPa. Calcium carbonate was purchased from Changzhou Lehuan Co., Ltd.

[0038] The above materials are put into a mixer and mixed. After being mixed evenly, they are poured into a feeder. The mixed materials are fed to a twin-screw extruder through the feeder. The speed of the feeder is 140 rpm. The mixed materials are melted, blended and extruded in the twin-screw extruder. The speed of the twin-screw extruder is 220 rpm and the temperature is 170°C. After the extruded polymer melt is cooled, it enters a pelletizer and is cut into uniform particles. After drying, the modified polyoxymethylene particles are obtained.

[0039] The evaluation method of the embodiment is as follows: the melt index is measured by Zwick Aflow melt index meter, the dried polyoxymethylene resin is preheated at 190°C for 5 minutes, and a load of 2.16 kg is applied for testing, and the test complies with ISO-1133 standard. The basic mechanical properties are measured by Zwick universal testing machine, and the tensile modulus and tensile strain are tested according to ISO-527; the notched impact strength is tested according to ISO-179-1 / 1e A. The notched impact strength of the modified polyoxymethylene particles is 7.62 kJ / m 2 The notched impact strength is increased by 62.1% compared with that before modification; the melt index is 7.54g / 10min, the tensile modulus is 2150MPa, and the tensile strain is 38%. The melt index and tensile modulus have not changed significantly.

[0040] Example 4

[0041] This embodiment 4 discloses a polyethylene modified polyoxymethylene composite material, which is prepared from the following raw materials by weight: 94.2 parts of polyoxymethylene resin, 5 parts of polyethylene, 0.5 parts of calcium carbonate, and 0.3 parts of antioxidant 168. The polyoxymethylene resin comes from Tianjin Bohai Yongli Chemical Co., Ltd., and its model is MC90. Its melt index is 7g / 10min, tensile modulus is 2200MPa, and notched impact strength is 4.7kJ / m 2 The polyethylene was purchased from Jilin Chemical Co., Ltd. Its melt index was 1.5 g / 10 min and its density was 0.917 g / cm 3 , the tensile breaking stress is 11MPa. Calcium carbonate was purchased from Changzhou Lehuan Co., Ltd.

[0042] The above materials are put into a mixer and mixed. After being mixed evenly, they are poured into a feeder. The mixed materials are fed to a twin-screw extruder through the feeder. The speed of the feeder is 180 rpm. The mixed materials are melted, blended and extruded in the twin-screw extruder. The speed of the twin-screw extruder is 260 rpm and the temperature is 200°C. After the extruded polymer melt is cooled, it enters a pelletizer and is cut into uniform particles. After drying, the modified polyoxymethylene particles are obtained.

[0043] The evaluation method of the embodiment is as follows: the melt index is measured by Zwick Aflow melt index meter, the dried polyoxymethylene resin is preheated at 190°C for 5 minutes, and a load of 2.16 kg is applied for testing, and the test complies with ISO-1133 standard. The basic mechanical properties are measured by Zwick universal testing machine, and the tensile modulus and tensile strain are tested according to ISO-527; the notched impact strength is tested according to ISO-179-1 / 1e A. The notched impact strength of the modified polyoxymethylene particles is 8.03 kJ / m 2 The notched impact strength is increased by 70.8% compared with that before modification; the melt index is 7.27g / 10min, the tensile modulus is 2200MPa, and the tensile strain is 37%. The melt index and tensile modulus have not changed significantly.

[0044] Example 5

[0045] This embodiment 5 discloses a polyethylene modified polyoxymethylene composite material, which is prepared from the following raw materials by weight: 91.9 parts of polyoxymethylene resin, 7 parts of polyethylene, 0.7 parts of calcium carbonate, 0.2 parts of antioxidant 168, 0.1 parts of antioxidant 616, and 0.1 parts of antioxidant 1076. The polyoxymethylene resin comes from Tianjin Bohai Yongli Chemical Co., Ltd., and its model is MC90. Its melt index is 11g / 10min, its tensile modulus is 2600MPa, and its notched impact strength is 6.3kJ / m 2The polyethylene was purchased from Jilin Chemical Co., Ltd. Its melt index was 2.5 g / 10 min and its density was 0.923 g / cm 3 , the tensile breaking stress is 15MPa. Calcium carbonate was purchased from Changzhou Lehuan Co., Ltd.

[0046] The above materials are mixed in a mixer, poured into a feeder after being mixed evenly, and the mixed materials are sent to a twin-screw extruder through the feeder, and the speed of the feeder is 140rpm. The mixed materials are melted, blended and extruded in the twin-screw extruder, and the speed of the twin-screw extruder is 220rpm and the temperature is 190℃. After the extruded polymer melt is cooled, it enters a pelletizer and is cut into uniform particles, and the modified polyoxymethylene particles are obtained after drying.

[0047] The evaluation method of the embodiment is as follows: the melt index is measured by Zwick Aflow melt index meter, the dried polyoxymethylene resin is preheated at 190°C for 5 minutes, and a load of 2.16 kg is applied for testing, and the test complies with ISO-1133 standard. The basic mechanical properties are measured by Zwick universal testing machine, and the tensile modulus and tensile strain are tested according to ISO-527; the notched impact strength is tested according to ISO-179-1 / 1e A. The notched impact strength of the modified polyoxymethylene particles is 8.22 kJ / m 2 The notched impact strength is increased by 30.5% compared with that before modification; the melt index is 7.88g / 10min, the tensile modulus is 2190MPa, and the tensile strain is 36%. The melt index and tensile modulus have not changed significantly.

[0048] Example 6

[0049] This embodiment 6 discloses a polyethylene modified polyoxymethylene composite material, which is prepared from the following raw materials by weight: 88.7 parts of polyoxymethylene resin, 10 parts of polyethylene, 1 part of calcium carbonate, 0.2 parts of antioxidant 616, and 0.1 parts of antioxidant 1076. The polyoxymethylene resin comes from Tianjin Bohai Yongli Chemical Co., Ltd., and its model is MC90. Its melt index is 11g / 10min, its tensile modulus is 2600MPa, and its notched impact strength is 4.7kJ / m 2 The polyethylene was purchased from Jilin Chemical Co., Ltd. Its melt index was 2.5 g / 10 min and its density was 0.923 g / cm 3 , the tensile breaking stress is 15MPa. Calcium carbonate was purchased from Changzhou Lehuan Co., Ltd.

[0050] The above materials are put into a mixer and mixed. After being mixed evenly, they are poured into a feeder. The mixed materials are fed to a twin-screw extruder through the feeder. The speed of the feeder is 160 rpm. The mixed materials are melted, blended and extruded in the twin-screw extruder. The speed of the twin-screw extruder is 240 rpm and the temperature is 180°C. After the extruded polymer melt is cooled, it enters a pelletizer and is cut into uniform particles. After drying, the modified polyoxymethylene particles are obtained.

[0051] The evaluation method of the embodiment is as follows: the melt index is measured by Zwick Aflow melt index meter, the dried polyoxymethylene resin is preheated at 190°C for 5 minutes, and a load of 2.16 kg is applied for testing, and the test complies with ISO-1133 standard. The basic mechanical properties are measured by Zwick universal testing machine, and the tensile modulus and tensile strain are tested according to ISO-527; the notched impact strength is tested according to ISO-179-1 / 1e A. The notched impact strength of the modified polyoxymethylene particles is 7.97 kJ / m 2 The notched impact strength is increased by 69.5% compared with that before modification; the melt index is 8.03g / 10min, the tensile modulus is 2150MPa, and the tensile strain is 38%. The melt index and tensile modulus have not changed significantly.

[0052] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.

Claims

1. A polyethylene-modified polyoxymethylene composite material, characterized in that: The raw material components include, by weight: 88.7-94.2 parts of polyoxymethylene resin, 5-10 parts of polyethylene, 0.3-1 parts of calcium carbonate, and 0.2-0.4 parts of antioxidant; The above components total 100 parts.

2. The polyethylene-modified polyoxymethylene composite material according to claim 1, characterized in that: The antioxidant may be one or more of antioxidant 1010 , antioxidant 1076 , antioxidant 168 , and antioxidant 616 .

3. The polyethylene-modified polyoxymethylene composite material according to claim 1, characterized in that: The polyoxymethylene resin has a melt index of 7-11 g / 10 min, a tensile modulus of 2200-2600 MPa, and a notched impact strength of 4.7-6.3 kJ / m 2 .

4. The polyethylene-modified polyoxymethylene composite material according to claim 1, characterized in that: The polyethylene melt index is 1.5-2.5 g / 10 min, and the density is 0.917-0.923 g / cm 3 , the tensile breaking stress is 11-15MPa.

5. The method for preparing the polyethylene-modified polyoxymethylene composite material according to claim 1, characterized in that: 88.7-94.2 parts of polyoxymethylene resin, 5-10 parts of polyethylene, 0.3-1 parts of calcium carbonate and 0.2-0.4 parts of antioxidant are put into a mixer and mixed. After being evenly mixed, the mixture is poured into a feeder. The mixture is sent to a twin-screw extruder through the feeder. The mixture is melt-blended and extruded in the twin-screw extruder. After the extruded polymer melt strips are cooled, they are cut into uniform particles in a pelletizer. After drying, the modified polyoxymethylene particles are obtained.

6. The method for preparing the polyethylene-modified polyoxymethylene composite material according to claim 5, characterized in that: The rotation speed of the feeder is 140-180 rpm, the rotation speed of the twin-screw extruder is 220-260 rpm, and the temperature of the twin-screw extruder is controlled at 170-200°C.

Citation Information

Patent Citations

  • Ultrathin composite powder reinforced polyformaldehyde materials and method for preparing same

    CN1664003A